PENGEMBANGAN SOAL-SOAL KONTEKSTUAL PADA MATA KULIAH ALJABAR LINEAR BERBASIS MATRIKS LESLIE - Ferryansyah Ferryansyah (Jurusan Pendidikan Matematika Universitas Borneo Tarakan, 2019)
Understanding the exact mathematical concepts in students can be obtained through an in-depth process by practicing existing problems in daily life known as contextual learning. Linear Algebra is one of the mathematics courses in the Department of Mathematics Education, Faculty of Teacher Training and Education, University of Borneo Tarakan. But in practicing problem solving students need contextual questions so that the learning abilities obtained by students are more meaningful and students can find out the usefulness of Linear Algebra courses in daily life, especially on matrix material. Eigenvalues and eigenvectors in matrix material are one sub material that can be associated with the Leslie matrix. The Leslie Matrix is a matrix used to predict the number and rate of growth of female population in the City of Tarakan. The development of contextual questions related to the Leslie matrix includes calculating the predicted number of female population growth in one of the kelurahans in the City of Tarakan in the next 5 years and calculating the prediction of the rate of female population growth in one of the kelurahans in the City of Tarakan in the next 5 years.